DECAF score at admission as a tool to predict clinical outcome in acute exacerbation of COPD - Gogul Mathialagan M; Jacinth Preethi J; Manikandan V; Vinoth R (Asian Journal of Medical Sciences, 2024)
Background: The Dyspnea, Eosinopenia, Consolidation, Acidemia, and Atrial Fibrillation (DECAF) score at presentation is designed to predict the risk of death in patients with chronic obstructive pulmonary disease (COPD). Aims and Objectives: To study the DECAF score at admission to predict the clinical outcome of the patients during hospitalization for acute exacerbation of COPD (AE-COPD). Materials and Methods: The study was conducted using a prospective cross-sectional observational study design in a tertiary care center in South India from April 2022 to March 2023. Patients were recruited based on specific inclusion and exclusion criteria. The data corresponding to the five variables of the DECAF score was obtained, and the relation to outcome measures such as survival, ventilation, and duration of stay was measured. Results: Two hundred consecutive patients were assessed. Based on the DECAF score, 102 patients (51%) were classified as low-risk, and this group had no mortalities. In the intermediate-risk group, the mortality rate was 7.4%; in the high-risk group, the observed mortality rate was 38.6%. The differences noted were significant statistically. Higher dyspnea grade as measured by extended Modified Research Council criteria was related to DECAF score was significant and with the outcome. Conclusion: Our study shows that the DECAF score at the initial presentation can be used as a reliable tool to predict the outcome of AE-COPD. Dyspnea grading can be used to predict mortality indirectly.